2007
DOI: 10.1128/aem.01635-06
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vibrio cholerae by Real-Time Nucleic Acid Sequence-Based Amplification

Abstract: A multitarget molecular beacon-based real-time nucleic acid sequence-based amplification (NASBA) assay for the specific detection of Vibrio cholerae has been developed. The genes encoding the cholera toxin (ctxA), the toxin-coregulated pilus (tcpA; colonization factor), the ctxA toxin regulator (toxR), hemolysin (hlyA), and the 60-kDa chaperonin product (groEL) were selected as target sequences for detection. The beacons for the five different genetic targets were evaluated by serial dilution of RNA from V. ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 55 publications
3
28
0
3
Order By: Relevance
“…As an alternative to PCR for molecular detection, real-time NASBA has been widely used for the detection of RNA vi- ruses, such as enterovirus and HIV (13,18,25); certain microbial pathogens, including Legionella species and Vibrio cholerae (7,16); and pathogens from food and environmental samples (3,20). However, only studies of small scope have been reported on the use of NASBA to detect Aspergillus species (14,36); nevertheless, the good diagnostic value of NASBA was demonstrated by those studies.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to PCR for molecular detection, real-time NASBA has been widely used for the detection of RNA vi- ruses, such as enterovirus and HIV (13,18,25); certain microbial pathogens, including Legionella species and Vibrio cholerae (7,16); and pathogens from food and environmental samples (3,20). However, only studies of small scope have been reported on the use of NASBA to detect Aspergillus species (14,36); nevertheless, the good diagnostic value of NASBA was demonstrated by those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies, performed to establish the use of RNA as proof of viability, employed heating (either autoclaving or boiling) of the cells (11). Some reports suggested that invA mRNA degrades rapidly in S. Typhimurium ATCC 14028 from 10 copies to less than 1 copy per CFU after 50 h of incubation in drinking and pond water (10).…”
Section: Discussionmentioning
confidence: 99%
“…As a powerful diagnostic tool, real-time NASBA has been used widely for detecting RNA viruses such as enterovirus and human immunodeficiency virus (27,31,39), certain microbial pathogens including Legionella species, Vibrio cholerae, etc. (18,30), and pathogens from food and environmental samples (11,36). However, only a few studies have reported using conventional NASBA to detect Candida spp.…”
Section: Vol 47 2009 Molecular Beacon Detection Of Bloodstream Infementioning
confidence: 99%